2013
DOI: 10.1016/j.bbamcr.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Calcium - a central regulator of pollen germination and tube growth

Abstract: Pollen tubes grow rapidly by very fast rates and reach extended lengths to bring about fertilization during plant reproduction. The pollen tube grows exclusively at its tip. Fundamental for such local, tip-focused growth are the presence of internal gradients and transmembrane fluxes of ions. Consequently, vegetative pollen tube cells are an excellent single cell model system to investigate cell biological processes of vesicle transport, cytoskeleton reorganization and regulation of ion transport. The second m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
179
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 239 publications
(183 citation statements)
references
References 136 publications
4
179
0
Order By: Relevance
“…Many of these physiological processes are interconnected, rendering the analysis of the Ca 2+ signaling cascades difficult. The current knowledge on generating Ca 2+ gradients and decoding Ca 2+ signatures in pollen tubes has recently been comprehensively reviewed (Konrad et al, 2011;Steinhorst and Kudla, 2012). Much less is known about the role of anions on pollen germination and tube growth performance (Tavares et al, 2011b).…”
Section: Correlation Between Anion and Ca 2+ Homeostasismentioning
confidence: 99%
“…Many of these physiological processes are interconnected, rendering the analysis of the Ca 2+ signaling cascades difficult. The current knowledge on generating Ca 2+ gradients and decoding Ca 2+ signatures in pollen tubes has recently been comprehensively reviewed (Konrad et al, 2011;Steinhorst and Kudla, 2012). Much less is known about the role of anions on pollen germination and tube growth performance (Tavares et al, 2011b).…”
Section: Correlation Between Anion and Ca 2+ Homeostasismentioning
confidence: 99%
“…Since Brewbaker and Kwack (1963) revealed that Ca 2+ is essential for in vitro pollen tube cultures, the relationship between Ca 2+ concentration ([Ca 2+ ]) and pollen tube growth has been extensively examined (Steinhorst and Kudla, 2013). In compatible pollination using pollen grains of transgenic Arabidopsis thaliana expressing a Ca 2+ sensor protein, a cytoplasmic [Ca 2+ ] ([Ca 2+ ] cyt ) increase was observed at the potential germination site and at the tip region of the pollen tube (Iwano et al, 2004(Iwano et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The use of liquid or agar-gelled medium with the various ingredients is the most common physical support to germinate pollen in vitro. Earlier investigations have shown the importance of different ingredients including Ca 2+ ions 2 , boron 3 , and sucrose 4 added to media for pollen germination of different plant species in vitro. A recent study shows that a solid support matrix such as a cellulose membrane placed on top of agarose gel resulted in a high percentage of Arabidopsis pollen germination in vitro 5 .…”
Section: Introductionmentioning
confidence: 99%